Combination of decentralized waste drying and SSF techniques for household biowaste minimization and ethanol production. (June 2016) - Sotiropoulos, A.; Vourka, I.; Erotokritou, A.; Novakovic, J.; Panaretou, V.; Vakalis, S.; Thanos, T.; Moustakas, K.; Malamis, D.
Graphical abstract: Highlights: Biowaste drying significantly reduces the mass and volume of household biowaste. Waste drying produces biomass which could be used for ethanol production. Seasonal variation to the chemical characteristics of household biowaste was observed. The combination of biowaste drying and SSF process for ethanol production is used for the 1st time. The SSF process needs to be further optimized in the future. Abstract: The results of the demonstration of an innovative household biowaste management and treatment scheme established in two Greek Municipalities for the production of lignocellulosic ethanol using dehydrated household biowaste as a substrate, are presented within this research. This is the first time that biowaste drying was tested at a decentralized level for the production of ethanol using the Simultaneous Saccharification and Fermentation (SSF) process, at a pilot scale in Greece. The decentralized biowaste drying method proved that the household biowaste mass and volume reduction may reach 80% through the dehydration process used. The chemical characteristics related to lignocellulosic ethanol production have proved to differ substantially between seasons thus; special attention should be given to the process applied for ethanol production mainly regarding the enzyme quality and quantity used during the pretreatment stage. The maximum ethanol production achieved was 29.12 g/L, approximately 60% of the maximum theoretical yield based on the substrate's sugar content. The use of the decentralized waste drying as an alternative approach for household biowaste minimization and the production of second generation ethanol is considered to be a promising approach for efficient biowaste management and treatment in the future.